Talking in clichés the use of stock phrases in discourse and communication - Bullo, Stella 1975-; Bousfield, Derek (Cambridge University Press, 2023)
"Fusing cutting-edge approaches of systemic-functional linguistics and discourse approaches with Interactional and Applied Pragmatics, this book explores the nature and role of clichés, reimagining this often-disparaged form of language as a means to efficient, effective communication and interaction"-- Provided by publisher.